Potential tuberculostatic agents: Micelle-forming copolymer poly(ethylene glycol)-poly(aspartic acid) prodrug with isoniazid - Silva, M.; Lara, A. S.; Leite, CQF; Ferreira, E. I. (Wiley-Blackwell, 2001)
With the objective of obtaining slow-acting isoniazid derivatives, of potential use as chemoprophylactics or chemotherapeutics in tuberculosis, the micelle-forming copolymer of poly(ethylene glycol)-poly(aspartic acid) prodrug with isoniazid was synthesized. The derivative obtained was found to be active in Mycobacterium Il(tuberculosis culture, with a minimal inhibitory concentration (MIC) 5.6 times lower than that of the tuberculostatic drug.
Keywords: potential tuberculostatic agent; isoniazid; prodrug; micelle-forming polymer; co-polymer poly(ethylene glycol)-poly(aspartic acid)